(untitled) (Research, Society and Development, 2022)
This research sought bringing the experiences of Public Security agents, who work in the Maria da Penha Patrol, on the coast of Paraná. With their reports, it is intended to verify how the violence against women’s confrontation is being carried out, the daily challenges they face, as well as understanding the dynamics of their work. The methodology used is a comprehensive qualitative research, in which data were collected through semi-structured interviews and then systematized by the NVIVO software. The results are presented according to the interviewed professionals’ stories. It is aimed to understand how they perceive the quality of services provided to women in situations of violence on the coast of Paraná. By reviewing their perspectives, some demands were raised, which contributes to the mapping of competencies and planning actions aimed to the development and empowerment of women victims of aggression.